(untitled) (International journal of medical sciences, 2025)
This scientific article presents the theoretical and practical significance of modern diagnostic methods used for the detection of infections and diseases of various etiologies. The study substantiates the importance of molecular biology techniques, immunological analyses, microscopy technologies, and clinical laboratory methods in achieving accurate identification of pathological conditions. Special attention is given to highly sensitive early detection approaches, patient-safety-oriented methods, and diagnostic algorithms that enhance the effectiveness of clinical decision-making. The article highlights the relevance of advanced diagnostics in assessing the course of infectious diseases, reducing the risk of complications, and improving therapeutic strategies.